LRRC45 contributes to early steps of axoneme extension - Kurtulmus, Bahtiyar; Yuan, Cheng; Schuy, Jakob; Neuner, Annett; Hata, Shoji; Kalamakis, Georgios; Martín-Villalba, Ana; Pereira, Gislene (Journal of cell science, 2018)
Skip to Next Section - Cilia perform essential signalling functions during development and tissue homeostasis. A key event in ciliogenesis occurs when the distal appendages of the mother centriole form a platform that docks ciliary vesicles and removes CP110-Cep97 inhibitory complexes. Here, we analysed the role of LRRC45 in appendage formation and ciliogenesis. We show that the core appendage proteins Cep83 and SCLT1 recruit LRRC45 to the mother centriole. Once there, LRRC45 recruits the keratin-binding protein FBF1. The association of LRRC45 with the basal body of primary and motile cilia in both differentiated and stem cells reveals a broad function in ciliogenesis. In contrast to the appendage components Cep164 and Cep123, LRRC45 was not essential for either docking of early ciliary vesicles or for removal of CP110. Rather, LRRC45 promotes cilia biogenesis in CP110-uncapped centrioles by organising centriolar satellites, establishing the transition zone and promoting the docking of Rab8 GTPase-positive vesicles. We propose that, instead of acting solely as a platform to recruit early vesicles, centriole appendages form discrete scaffolds of cooperating proteins that execute specific functions that promote the initial steps of ciliogenesis.
Gesehen am 13.11.2019